Tuning the Angular Characteristics of Biomimetic Antenna Arrays - Ines Dorsch; Dominik Schwarz; Sarah Forster; Christian Waldschmidt (IEEE Open Journal of Antennas and Propagation, 2023)
The angle estimation capabilities of radar sensors are strictly linked to the antenna spacing between the array elements. A larger array aperture corresponds to a smaller beam width or in terms of the angle estimation a higher phase sensitivity. So-called Biomimetic Antenna Arrays (BMAAs) provide the opportunity to shape the angular characteristics with more degrees of freedom. In this work, the concept and the design process of a tunable BMAA are presented. By electronically tuning varactor diodes, such an array can adapt its angular characteristics depending on the direction-of-arrival (DoA) and signal strength of a radar target. The theoretical requirements for the desired task are examined with general S-parameter simulations. Extensive circuit simulations of a proposed architecture unveil a variety of achievable designs of tunable BMAAs. Radar measurements of different implementations in the 77 GHz range and the theoretical analysis are in good agreement. The measurements show, inter alia, that the operational point of maximum biomimetically-increased phase sensitivity can be tuned over a range of 40° around the boresight direction, or that the power losses associated with BMAAs can be decreased by approximately 12 dB for weak radar targets, improving the detection capabilities.